A importância do ICMS na receita pública do Estado do Ceará - Lima, Francisco Dorneles (2010)
Reported the importance of ICMS in public revenue of the State of Ceará. Describes and analyzes the Brazilian tax dispute, explain charge, such as the main source of funds to finance public spending. Emphasizes that the state of Ceará, most financial income defined as income derives from public tax revenues. Of that amount, representing his own effort, show that the payments arising from the ICMS accounted for more than 94%, according to notes found in the years 2007 and 2008 timeframe of the research. Points out that in the period considered, the other tax jurisdiction of the State of Ceará are very modest in terms of revenue to the Treasury, except for minor significance with respect to IPVA. Justifies the supremacy of the ICMS is a direct function of its large base, the diversity of internal and interstate rates applied and the actual structure of taxation, covering the regimes of anticipation and replacement tax. There, in recent years, increasing tax revenues in Ceará, a fact that is due to the growth of the main economic sectors in the state and improvement of the administration and tax collecting machine. Demonstrates relative significance of ICMS for municipal budgets, since the state is constitutionally obliged to pass on to the municipalities 25% of the collected tax. It remained also substantiated the importance of the ICMS, not only by their function or tax-raising, but by a range of usefulness that it is within the various government projects, and is much used as an instrument of economic policy of the State of Ceará.